2015
DOI: 10.4049/jimmunol.1400319
|View full text |Cite
|
Sign up to set email alerts
|

Defective Selection of Thymic Regulatory T Cells Accompanies Autoimmunity and Pulmonary Infiltrates in Tcra-Deficient Mice Double Transgenic for Human La/Sjögren’s Syndrome-B and Human La-Specific TCR

Abstract: A human La/SS-B (hLa)-specific TCR/hLa neo-self antigen double transgenic mouse model was developed and used to investigate cellular tolerance and autoimmunity to the ubiquitous RNA-binding La antigen often targeted in systemic lupus erythematosus and Sjögren's syndrome. Extensive thymic clonal deletion of CD4+ T cells occurred in H-2k/k double transgenic mice presenting high levels of the I-Ek-restricted hLa T cell epitope. In contrast, deletion was less extensive in H-2k/b double transgenic mice presenting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…T lymphocytes have been described in the human and rodent conjunctiva13, and ocular surface T cells play a critical pathogenic role in DED, the commonest clinical manifestation of ocular surface inflammation222324252627282930. Here, we have used impression cytology and flow cytometry to characterize recirculating (naïve, T CM , T EM , T EMRA , T RCM ) and non-recirculating (T RM ) T cell subsets (Figs 1A and 2A) in the healthy human ocular surface and in patients with DED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T lymphocytes have been described in the human and rodent conjunctiva13, and ocular surface T cells play a critical pathogenic role in DED, the commonest clinical manifestation of ocular surface inflammation222324252627282930. Here, we have used impression cytology and flow cytometry to characterize recirculating (naïve, T CM , T EM , T EMRA , T RCM ) and non-recirculating (T RM ) T cell subsets (Figs 1A and 2A) in the healthy human ocular surface and in patients with DED.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental rodent DED, T cells are implicated in disease pathogenesis and adoptive transfer of pathogenic T cells is sufficient to impart DED in naïve recipients2324252627323637. Although the T-cell immunosuppressant cyclosporine A is a cornerstone of DED therapy, the direct involvement of T cells in human DED is harder to demonstrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H‐2 k/k .Thy1.1 +/+ congenic mice to generate heterozygous hLa transgenic (hLa Tg) or non‐Tg H‐2 k/k Thy1.1 +/+ and H‐2 k/b Thy1.1 +/+ recipient mice. 3B5.8 + hLa‐specific TCR Tg mice described previously were crossed to Tcra –/– (B6.129S2‐ Tcra tm1Mom /J; Jackson Laboratory) and B6.H‐2 k congenic mice to generate B6. 3B5.8 +/– .Tcra –/– .H‐2 k/k and B6.…”
Section: Methodsmentioning
confidence: 99%
“…Using mice expressing transgenic (Tg) human La (hLa) with ubiquitous, nuclear distribution at physiological levels, we have previously reported detectable immunological tolerance in hLa‐specific CD4 + T cells, but not in B lymphocytes . Further studies revealed that human La‐specific T cells in double Tg mice for an I‐E k ‐restricted T cell receptor (TCR) specific for hLa 67–76 peptide and the hLa neo‐self‐antigen undergo drastic but incomplete thymic clonal deletion . A portion of residual, hLa‐specific thymocytes in these mice developed into natural thymic regulatory T cells (T reg ), and the mice displayed high proportions of forkhead box P3 (FoxP3)‐expressing, hLa‐specific CD4 + T cells in peripheral lymphoid organs that functioned to maintain immunological self‐tolerance and prevent autoimmune lung pathology.…”
Section: Introductionmentioning
confidence: 99%